Food and Fitness: Myths and Truths - Linda B. Bobroff (EDIS, 2006)
Revised! FCS-8100, a 5-page fact sheet by Linda B. Bobroff, helps readers make good choices for their health and fitness in the face of inconsistent and confusing messages from mass media sources today. Information is provided through a food and fitness quiz. This version is updated with references to the USDA MyPyramid eating plan and adjusts recommendations for fitness drinks. This version also includes additional sources for finding reliable information. Published by the UF Department of Family Youth and Community Sciences, April 2006.